Digital identity, an emergent legal concept : the role and legal nature of digital identity in commercial transactions / by Clare Sullivan. - Sullivan, Clare Linda (The University of Adelaide Press, 2011)
This is the first full-length study of digital identity in a transactional context, from a legal perspective. The functions and legal nature of digital identity are analysed using real examples which highlight the implications for individuals, businesses and government. The findings have the potential to fundamentally change the way digital identity is legally and commercially regarded.